Intelligence and literary fiction: how novels can improve our (understanding of) intelligence - Nünning, Vera (Intelligence, 2022)
Although most people would agree that literary works, especially ‘classics’ such as books by Goethe or Shakespeare, contribute to education, there is a lack of research on the relationship between literature and intelligence. In spite of repeated assertions about the importance of reading good books, there are only a few studies examining the advantages that are conferred by reading works of fiction. Yet there are good reasons to look at literary works in order to better understand what intelligence is, to gain insights into different kinds of intelligence, and even to enhance readers’ interpersonal cognitive abilities. After a brief discussion of the relationship between literature and intelligence, this chapter presents the analyses of two novels to show what insights literary works can provide into different kinds of intelligence, such as the (meta)cognitive abilities which enable us to understand the thoughts and intentions of other human beings and to attribute mental states to them, and emotional intelligence that is based on an affective ability enabling us to empathise and feel with others. The interpretation of Ian McEwan’s Machines Like Me (2019) and Kazuo Ishiguro’s Klara and the Sun (2021) focuses on these kinds of intelligence, also exploring some differences between ‘artificial’ and human intelligence. In a next step, the analysis of the two novels serves as a point of reference for outlining the experiences readers of literary works can have with regard to intelligence. In addition to highlighting the mental processes that usually remain hidden and allowing insights into successful and unsuccessful modes of problem solving, literary works can question received knowledge about intelligence and provide experiences that can improve readers’ cognitive abilities. The brief conclusion revolves around some key questions that the novels raise about the connection between intelligence, wisdom and ethics.
Gesehen am 05.10.2022